Entre écosystèmes et territoires : quelle planification pour les espaces relevant de la GIZC ? - Bernard Drobenko (VertigO)
Planning of coastal areas reveal a real complexity due to their domains diversity and to the definition of their perimeters of intervention. In addition the planning requires highly variable integrated approaches that can have different opposability. While the integrated maritime policy focuses on the economic aspects, it is important to surpass this single objective and to define in this context the conditions that will clarify the legal framework. The aim of this paper is to identify what can be the future of coastal area planning if a real protection of the environment is integrated. In order to tend toward an effective ICZM (Integrated Coasted Zone Management) the proposed approaches are based on an evaluation and on indicators shared by the different actors of the coastal development monitoring.